Climate Information for Food Security - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
Robert Zougmoré, who is the West Africa Regional Program Leader for the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS), discusses the climate-related challenges farmers in West Africa face, and how forecasts and other types of information can improve decision making. Interview and production: Francesco Fiondella, International Research Institute for Climate and Society